The Transcendent Unity Behind the Diversity of Religions and Religiosity in the Perspective of Perennial Philosophy and Its Relevance to the Indonesian Context - M. Baharudin; Muhammad Aqil Luthfan (Walisongo: Jurnal Penelitian Sosial Keagamaan, 2017)
This study is conducted to answer an important question: is there any transcendent unity behind the diversity or plurality of religions and religiosity? This question will be answered through perennial philosophy approach. The study found that, according to perennial philosophers, there is a transcendent unity behind the diversity or plurality of religions and religiosity. This transcendent unity is seen in ‘the common vision’, or what in Islam is called the ‘basic message of religion’, namely ‘submission’ to always fear God and live His presence in everyday life. Further, the perennial philosophers argue that the True God is one; therefore, all religions emerging from the One are in principle the same for they come from the same source. In other words, the diversity of religions and religiosity lies only in the exoteric level, and all religions actually have a transcendent unity in the esoteric level. However, in this case, the perennial philosophers do not mean to unify or equate all religions. In fact, they try to open a way to a spiritual ascent through the reviving of the religious traditions in every religion.